An all ambient, room temperature–processed solar cell from a bare silicon wafer. Issue 3 (14th March 2023) - Okamoto, Kazuya; Fujita, Yutaka; Nishigaya, Kosuke; Tanabe, Katsuaki
Abstract: Solar cells are a promising optoelectronic device for the simultaneous solution of energy resource and environmental problems. However, their high cost and slow, laborious production process so far severely hinder a sufficient widespread of clean, renewable photovoltaic energy as a major alternative electricity generator. This undesirable situation is mainly attributed to the fact that photovoltaic devices have been manufactured through a series of vacuum and high-temperature processes. Here we realize a poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS)/Si heterojunction solar cell fabricated only in ambient and room temperature conditions from a plain Si wafer, with an over 10% energy conversion efficiency. Our production scheme is based on our finding that PEDOT:PSS photovoltaic layers actively operate even on highly doped Si substrates, which substantially mitigates the condition requirements for electrode implementation. Our approach may pave the way for facile, low-cost, high-throughput solar cell fabrication, useful in various fields even including developing countries and educational sites.